Exercise prescription a case study approach to the ACSM guidelines - Swain, David P.; Leutholtz, Brian C. (Human Kinetics, 2007)
A case study approach to exercise prescription, presenting the information needed to prepare for certification by the ACSM. Topics covered include: the adoption of VO2 reserve as the basis for writing exercise prescriptions; and prescribing exercise to special cases such as pregnant women